Les archives en milieu muséal: le cas du Musée McCord - Cartier, François (Archives, 2005)
Keywords: Archives; Musée McCord; Musées

Le projet de sauvegarde de la collection Bens Delicatessen. Bien plus que les archives du smoked meat! - Cartier, François (Archives, 2008)
Keywords: Archives; Confédération des syndicats nationaux; Musée McCord; Musées; Restaurant

L’archive littéraire à la rescousse de l’histoire: le cas des Comédies du Statu quo (1834) - Desjardins, Nancy (Archives et fabrique du textile littéraire, 2001)
Keywords: Archives; Papineau, Louis-Joseph; Rébellions

A Heuristic Archive: Jean-Paul Gill's Red Light Photographs - Guillaume, Philippe (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Archives; Patrimoine; Photographie; Quartiers; Saint-Laurent (quartier)

Révolution dans les archives...et dans la reconstitution du passé - Deslandres, Dominique (Les cahiers des Dix, 2023)
Keywords: Archives

L’ère des archives québécoises sur le Web - Robert, Mario (Cap-aux-Diamants, 2014)
Keywords: Archives; Archives municipales

Les procès en sorcellerie, des archives longtemps négligées : le cas de Montréal - Pettigrew, Stéphanie (Revue d'histoire de la Nouvelle-France, 2023)
Keywords: Archives; Tribunaux

''Au-delà du syndrome de la «citation payante»'': les archives vivantes et la recherche réciproque en histoire orale - High, Steven (Revue d'histoire de l'Amérique française, 2015)
Keywords: Archives; Histoire

La revue Archives à travers ses vingt dernières années d’existence, 1988-2008 - Gagnon-Arguin, Louis (Archives, 2009)

L'odyssée des archives de la Société Historique de Montréal - Robert, Mario (Montréal en tête, 2019)
Keywords: Archives; Société historique de Montréal

Female Authorship, Incomplete Archives, and the Periodical Press in Nineteenth Century Montreal: The Case of Rosanna Mullins Leprohon - Cabajsky, Andrea (Port Acadie, 2022)
Keywords: Archives; Femmes; Écrivains

Recovering Identities from the Judicial Archives of Quebec - Olson, Sherry; Poutanen, Mary Anne (Histoire sociale / Social History, 2024)
Keywords: Archives; Enfants; Famille; Femmes

La nuit de feu des livres et des archives du Parlement - Gallichan, Gilles (Bulletin d'histoire politique, 2013)
Keywords: Archives; Incendies; Parlement; Torys; Émeutes

L’archive et l’invention littéraire: le cas des Mystères de Montréal d’Auguste Fortier (1893) - Ducharme, Nathalie (Archives et fabrique du textile littéraire, 2001)

Les archives de la Société historique de Montréal. La contribution de la Société historique de Montréal à la sauvegarde du patrimoine archivistique montréalais - Lebeau, Mireille (Montréal en tête, 2008)
Keywords: Archives; Conservation; Histoire; Patrimoine; Société historique de Montréal

L’apport de François Beaudin: la mise en place du rapport Deschênes - Baillargeon, Diane (Archives, 2017)
Keywords: Université de Montréal

Théâtre à Montréal, 1825-1930: un récit visuel mettant en scène des documents patrimoniaux - Léger, Danielle (Archives, 2019)
Keywords: Cartes et plans; Histoire; Patrimoine; Théâtre

Historienne, mentore, libre-penseuse: réflexions autour de l'oeuvre d'Andrée Lévesque - Fahrni, Magda (Profession historienne? Femmes et pratique de l’histoire au Canada français, XIXe-XXe siècles, 2023)
Keywords: Archives; Femmes; Histoire

Que reste-t-il… des archives de nos premières émissions? - Moreau, Jean-Paul (Cap-aux-Diamants, 2002)
Keywords: Télévision

Photogenic Montreal: Activisms and Archives in a Post-Industrial City - Langford, Martha; Sloan, Johanne (McGill-Queen's / Beaverbrook Canadian Foundation Studies in Art History Series, 2021)
Keywords: Conservation; Patrimoine; Photographie; Quartiers

The Christian Pavilion at Expo 67: Notes from Charles Gagnon's Archive - Kin Gagnon, Monika (Expo 67: Not Just a Souvenir, 2010)
Keywords: Cinéma; Expositions

Boxing Time: Landscape, Feminism and the Archive in Selected Works by Angela Grauerholz - Brock, Lesley L. (Université Concordia, 2004)
Keywords: Paysages; Photographie

Identities, Communities, and the Infrastructures of History: Creating Canadian Jewish Archives in the 1930s and the 1970s - Menkis, Richard (History, Memory, And Jewish Identity, 2015)
Keywords: Congrès juif canadien; Histoire; Juifs

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Keywords: Danse; Femmes; Histoire; Musicien; Musique

Westmount public library: Celebrating 125 years (The Westmount Historian, 2024)
Keywords: Archives; Patrimoine; Vitraux; Westmount

Regards sur une Bible hébraïque, une Bible polyglotte et une Bible de Genève conservées par Bibliothèque et Archives nationales du Québec - Crevier Denommé, Isabelle (Ouvrages phares de la Réforme & de la Contre-Réforme dans les collections montréalaises, 2014)
Keywords: Bibliothèque nationale

Reading the Multimedia Archive Surrounding Montreal's Post-War LGBTQ Bars: A Genealogical Return to Madame Arthur and Il était une fois dans l'Est - Pidduck, Julianne (Quebec Studies, 2015)
Keywords: Alcool

À la découverte du Fonds Albéric Bourgeois (1876-1962): thématiques d'une société en transformation, 1899-1957 - Hardy, Dominic; Godin-Laverdière, Julie-Anne; Perron, Nancy (Quand la caricature sort du journal: Baptiste Ladébauche, 1878-1957, 2015)
Keywords: Archives; Bourgeois, Albéric; Caricature; Histoire

Une “vaillante phalange” contre “vieux pontifes”. La réception des Soirées du Château de Ramezay dans le journal Les Débats - Cellard, Karine (Archives et fabrique du textile littéraire, 2001)
Keywords: Ramezay (château de)

Ironie, sarcasme et dérision dans Le Canadien (1806-1810) - Laquerre, Marie-Lise; Massé, Stéphanie (Archives et fabrique du textile littéraire, 2001)
Keywords: Humour

Regards catholiques sur les villes québécoises: une haine à géométrie variable (1918-1939) - Bérubé, Harold (Archives de sciences sociales des religions, 2014)

The Pastness of Allô Police - Straw, Will (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Criminalité; Photographie

Erase and See: The Photogénie of a Metropolis in Progress - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Paysages; Photographie

Architecture, Photography, and Power: Picturing Montreal, 1973-74 - Imogen Hammond, Cynthia (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; McConnell, John Wilson; McConnell, John Wilson (maison); Patrimoine; Photographie; Shaughnessy (maison); Van Horne (maison); Van Horne, William

Through the Lens of Edith Mather: Photographing Demolition and the Transforming City - Southcott, Tanya (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Conservation; Femmes; Patrimoine; Photographie; Rues

Re-activations: Alain Chagnon’s Plateau-Mont-Royal in Translation - Langford, Martha (Photogenic Montreal: Activisms and Archives in a Post-Industrial City, 2021)
Keywords: Photographie; Plateau Mont-Royal; Quartiers

l'Institut canadien de Montréal: un avant-goût des grands principes de la bibliothèque publique moderne - Lefebvre, Michèle (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Institut canadien

Du journal à l'oeuvre « Écrire, mon secret, ma captivité, ma vie », Yves Navarre - Lannegrand, Sylvie (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Écrivains

Genèse du cycle de « La batèche » de Gaston Miron: de la noirceur aux rives de l'aube nouvelle - Villeneuve, Karine (Revue de Bibliothèque et Archives nationale du Québec, 2011)
Keywords: Miron, Gaston; Poésie

La Revue populaire et Le Samedi – Objets de diffusion de la modernité photographique au Québec, 1935-1945 - Tousigant, Zoë (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie

Montréal érotique : pin-up et imagerie de nus chez le photographe de presse Conrad Poirier, 1912-1968 - Godin-Laverdière, Julie-Anne (Revue de Bibliothèque et Archives nationale du Québec, 2013)
Keywords: Photographie; Poirier, Conrad

Les passerelles internationales de la maison d'édition Parti pris - Fabre, Gérard (Revue de Bibliothèque et Archives nationale du Québec, 2010)
Keywords: Godin, Gérald; Idéologies; Parti Pris; Édition

''Il y a des chose qu'une personne cultivée ne peut ignorer''- Le Bulletin de la Société d'étude et de conférences (1915-1967): sa genèse, ses actrices et son contenu. - St-Laurent, Fanie (Revue de Bibliothèque et Archives nationale du Québec, 2012)
Keywords: Femmes

La Gazette littéraire de Montréal 1778-1779 - Doyon, Nova; Cotnam, Jacques (L'archive littéraire au Québec, 2010)
Keywords: Gazette Littéraire de Montréal; Mesplet, Fleury

La guerre de 1812: Journal de Jacques Viger - Viger, Jacques; Andrès, Bernard (L'archive littéraire au Québec, 2012)
Keywords: Maires; Viger, Jacques

La Grande Guerre de Paul Caron. Chroniques d'un légionnaire canadien-français (1914-1917) - Richard, Béatrice (L'archive littéraire au Québec, 2015)
Keywords: Guerre

David Ross McCord (1844-1930): Imagining a Self, Imagining a Nation - Harvey, Kathryn Nancy (Université McGill, 2006)
This thesis is about the life of David McCord and the contribution he made to Canadian public memory as founder of the McCord Museum of National History. In his McGilI-sponsored museum, founded in 1921, McCord sought to promote a myth of Canadian origins with narration provided by the objects of his personal collection. Integral to this history was the story of the McCord family, their arrival on this continent and their rise to social prominence. In McCord's version of Canadian history, family and personal myth were conflated with that of nation. Viewed through the prism of his collecting and museum work, McCord's life does not easily fit the Carlylean frame adopted by most biographers. In Canadian biographical writing by historians, the 'truth' about a person's life is revealed by following the modernist recipe of painstakingly recreating a detailed chronology of the individual's life. The approach followed here is an important departure from traditional political biography. Entry into McCord's life does not occur at his biological birth date, but at the moment of his own self-fashioned 'birthing', with the opening of the museum realized near the end of his life. In this biographical strategy, McCord's museum acts as a theatre of memory, where fragments of his life story are reassembled to create a narrative of national origins and of personal redemption. In his selection of objects and their display, and in the creation of an archive and the museum itself, McCord left a very elaborate and lasting record of his response to a set of changes associated with industrialization, a process which, in his lifetime, radically transformed the Montreal of his parents' generation. This thesis traces the connection between the creation of a public museum, founded to promote a collective vision of the Canadian past, and the private world of one collector whose collecting practice was defined as much by his own desire to remember and be remembered as it was by the kinds of objects he collected. What makes David McCord's life and collection so compelling is the opportunity it provides from understanding national history from the intimate perspective of one individual.
Keywords: McCord (famille); McCord, David Ross; Musée McCord; Musées